Manajemen Pemberdayaan Wakaf untuk Meningkatkan Kesejahteraan Umat di Yayasan Pemberdayaan Insan Mandiri (YAPIM) Ciledug Kota Tangerang - Wajiri Wajiri; Ahmad Asrof Fitri; Meity Suryandari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This thesis examines the management of waqf empowerment at Yayasan Pemberdayaan Insan Mandiri (YAPIM) in Ciledug, Tangerang. The focus is to understand how waqf empowerment is implemented and to identify both supporting and inhibiting factors. The aim is to see how waqf management contributes to community welfare and what challenges are faced in practice. The research uses a qualitative approach with structured interviews involving ten informants, including YAPIM’s management and local community leaders, supported by observation and documentation. Findings show that YAPIM has developed a cash waqf program to acquire land for community needs. The land is utilized to build dormitories for orphans and underprivileged groups, showing the social value of waqf. At present, waqf empowerment remains in the developmental stage due to the lack of a dedicated institution managing waqf assets. Its use focuses on education and the economy, though obstacles include limited organizational capacity and public hesitation. To ensure sustainability, the study recommends training for nazhir (waqf managers) to improve professionalism and strengthen waqf management.